Agentive Semiotics as a Methodological Framework for a Pedagogy of Understanding (Global Journal of Human-Social Science, 2025)
This article proposes agentive semiotics as a methodological framework for a pedagogy of understanding that empowers student agency and reconfigures the teaching role. From a perspective that conceives meaning as the result of the interaction between agent, agenda, and context, it critiques applicationism, the commercial orientation of materials, and the uncritical adoption of non-situated models for limiting critical thinking and self-regulation. It proposes an analytical model that integrates cognitive, affective, and situational dimensions, promoting the de-automatization of practices, the formulation of meaningful questions, and the development of rhizomatic "lines of flight" that open up creative and collective learning possibilities. The proposal culminates in strategies to anchor understanding in lived experience and narrative, understanding education as a living, critical, and humanized process, capable of transforming both pedagogical practices and the subjectivities that inhabit them.
Keywords: agentive semiotics; pedagogy of understanding; student agency; situated models; deautomatization; lines of flight; narrationality